Innate Activation of IFN-γ—iNOS Axis During Infection With Salmonella Represses the Ability of T Cells to Produce IL-2 - Yadav, Jitender; Dikshit, Neha; Ismaeel, Sana; Qadri, Ayub (Frontiers in Immunology, 2020)
Pathogenic Salmonella serovars are a major cause of enteric illness in humans and animals, and produce clinical manifestations ranging from localized gastroenteritis to systemic disease. T cells are a critical component of immunity against this intracellular pathogen. The mechanisms by which Salmonella modulates T-cell – mediated immune responses in order to establish systemic infection are not completely understood. We show that infection of mice with Salmonella enterica serovar Typhimurium (S.Typhimurium) suppresses IL-2 and increases IFN- and IL-17 production from T cells activated in vivo or ex vivo through the T cell receptor. Infection with S.Typhimurium brings about recruitment of CD11b+Gr1+ myeloid derived suppressor cells (MDSCs) to the spleen. Ex vivo depletion of these cells restores the ability of activated T cells to produce IL-2 and brings secretion of IFN- and IL-17 from these cells back to basal levels. The reduction in IL-2 secretion is not seen in IFN--/- and iNOS-/- mice infected with Salmonella. Our findings demonstrate that sustained innate activated IFN- production during progression of infection with Salmonella reduces IL-2 – secreting capability of T cells through an iNOS-mediated signaling pathway that can adversely affect long term immunity against this pathogen.